Tecnologia assistiva no Brasil: uma análise das ações da FINEP, período 2005 a 2008 - Almeida, Maria Paula Cardoso Matos de (2015)
From the importance of the issue ‘people with disabilities’ is gaining on the agenda of Brazilian public policies in recent years this present research has aimed to analyze the actions taken in Finep in the period 2005 to 2008 whose theme is the Assistive Technology (AT) to verify if such actions generated the effective introduction of innovative products, services and processes in the consumer market of AT. The methodology used was the Grounded Theory and the primary source of data and information was obtained on Finep. The research also presents examples of how public policies for TA are being implemented in the European Union and Australia. The study mapped the main difficulties faced by institutions and companies dedicated to innovative projects of AT for the introduction of assistive products on production lines and provided a reflection on the causes and suggestions on the most effective and direct participation of those involved and the continuity of actions for achieving the desired results in AT actions supported by Finep. There is, however, a gap between research, pilot batch or proof of concept and the actual production of goods and assistive services and there are several reasons identified in the research that contribute to this gap, for example, the profile of the companies and its propensity to risk, since the AT project execution cycle takes several steps, and therefore time to obtain a prototype able to start and marketing.